Proposed Development Strategy for Nasi Ayam Jagoan (The Indonesian Journal of Business Administration, 2015)
Abstract- Nowadays, the phase and lifestyle changes rapidly especially in Jakarta. This is affecting the food and beverage industry. Particularly with the fast growth of internet technology and awareness of healthy lifestyle trends made food provider competing in this emerging industry. NasiAyamJagoan is a small home-based industry with Hainan Chicken Rice as their specialties. The business issue faced by NasiAyamJagoan is lack of market penetration and stagnant sales for the past three years. Beside, Lack of clear strategic planning and business development made NasiAyamJagoan business not less growth. Analyzed both external and internal using PEST analysis, Porter’s Five Forces, Canvas Business Model analysis and Resource-based View. External and internal analysis will generate SWOT items which used for business strategy. SWOT items used for EFAS and IFAS calculation which presented in IE matrix. The results of IE matrix shows that NasiAyamJagoan in fourth cell categorized as grow and build. For those reason, QSPM calculation needed and generates an intensive strategy (market penetration, market development, product development). TOWS matrix conduct to apply as proposed new business model canvas. Therefore, NasiAyamJagoan must increase market penetration, expand market share, develop new product, improve marketing and promotion, increase sales and profit, and also to remain competitive. Keywords: BusinessStrategy, MarketPenetration, IntensiveStrategy, BusinessModel Canvas